X-ray lasers - Elton, Raymond C., 1932- (Academic Press, 1990)
The first in its field, this book is both an introduction to x-ray lasers and a how-to guide for specialists. It provides new entrants and others interested in the field with a comprehensive overview and describes useful examples of analysis and experiments as background and guidance for researchers undertaking new laser designs. In one succinct volume, X-Ray Lasers collects the knowledge and experience gained in two decades of x-ray laser development and conveys the exciting challenges and possibilities still to come. _Add on for longer version of blurb_M> The reader is first introduced to the technical challenges unique to the design and operation of lasers in the "vacuum" region of the spectrum, where the atmosphere is highly absorbent and optics are--at best--unconventional. A discussion of the basic principles for and limitations in achieving significant x-ray amplification, as well as descriptions of gain measurement techniques and instrumentation follows. Various approaches for pumping media to x-ray gain conditions are also analyzed, and descriptions of experimental progress are included wherever possible. The book concludes with a description and comparison with alternate sources and applications for an x-ray laser. _promo copy used by TJE_ This work is both an introduction to x-ray lasers and a how-to guide for specialists. It provides new entrants and others interested in the field with a comprehensive overview and describes useful analyses and experiments as guidance for researchers undertaking new laser designs. Key Features * Provides first comprehensive treatment of lasers for wavelengths shorter than the near-ultraviolet 2000 * Contains descriptions and comparisons with alternate sources * Includes a section describing possible applications * INCLUDED IN #01011 * INCLUDED IN APP SCI & ENG, JULY 90 * INCLUDED IN APPLIED SPECTROSCOPY, AUGUST 90 * INCLUDED IN OE REPORTS, AUGUST 90 * INCLUDED IN APPLIED OPTICS, SEPT 90 * INCLUDED IN IEEE LEOS NEWSLETTER, OCTOBER 90 * INCLUDED IN OPTICS NEWS, OCTOBER 90 * INCLUDED IN OE REPORTS, JANUARY 91